Effect of Ultrasound-Enhanced Transdermal Drug Delivery Efficiency of Nanoparticles and Brucine. (4th December 2017) - Zhang, Nongshan; Wu, Yiyun; Xing, Runlin; Xu, Bo; Guoliang, Dai; Wang, Peimin
Abstract : Brucine is the active component in traditional Chinese medicine "Ma-Qian-Zi" (Strychnos nux-vomica Linn), with capabilities of analgesic, anti-inflammatory, anti-tumor and so on. It is crucial how to break through the impact of cuticle skin which reduces the penetration of drugs to improve drug transmission rate. The aim of this study is to improve the local drug concentration by using ultrasound. We used fresh porcine skin to study the effects of ultrasound on the transdermal absorption of brucine under the influence of various acoustic parameters, including frequency, amplitude and irradiation time. The transdermal conditions of yellow-green fluorescent nanoparticles and brucine in skin samples were observed by laser confocal microscopy and ultraviolet spectrophotometry. The results show that under ultrasonic conditions, the permeability of the skin to the fluorescent label and brucine (e.g., the depth and concentration of penetration) is increased compared to its passive diffusion permeability. The best ultrasound penetration can make the penetration depth of more than 110 microns, fluorescent nanoparticles and brucine concentration increased to 2-3 times. This work will provide supportive data on how the brucine is better used for transdermal drug delivery (TDD).